Parâmetros seminais e extração de RNA espermático de mico-leão-de-cara-dourada (Leontopithecus chrysomelas) - Bacher, Patrícia Hergert (2016)
The Golden-headed lion tamarin (Leontopithecus chrysomelas) is an endemic primate from Atlantic Forest threatened with extinction. Amongst the conservational efforts addressed towards the species is the use of reproductive biotechnologies as a strategy of genetic resources preservation and assurance of captive and natural population´s viability. The success of the reproductive biotechnologies still depends on the detailed knowledge despite the reproductive aspects, the investigation of factors that may influence the reproductive success and the establishment of specific-species protocols. The cryopreservation of semen is the most widely used approach for wild species. However, one major challenge associated to the appliance of neotropical primate´s samples consists in the formation of seminal clots, which invalidates the use of great quantity of gamete in most reproductive procedures. The golden-headed lion tamarin has become a promising model among threatened neotropical primates and aiming to contribute with the development of reproductive technologies, this essay had the objective of initiate investigations concerning the molecular and seminal factor which may have an effect on the reproductive potential of sexually mature males of Leontopithecus chrysomelas. Therefore, the animals kept at the Fundação Parque Zoológico de São Paulo, São Paulo, Brazil, were divided into two groups, “Old” (mean age 11,6 years; n=6) and “Young” (mean age 4,8 years, n=6) to execute the semen collection and evaluation of the seminal parameters (concentration, motility, plasmatic and acrosome membrane integrity, mitochondrial cytochemical activity and morphology). The analysis of seminal parameters pointed out significant differences between the older and younger subjects despite the plasmatic membrane integrity (p=0,049), acrosome integrity (p=0,009) and for Class IV mitochondrial activity (p=0,026). The regression analysis showed that the age, as well as the weight of the individuals, have a negative influence over the quality of these parameters. Therefore, aiming to contribute with the development of new reproductive techniques and to improve the spermatic viability, a protocol of sperm selection by Percoll discontinuous gradient was tested. However, even though efficient for gamete isolation from other seminal component, the protocol did not show significant improvement of the parameters, reevaluated after selection, suggesting needing of methodological adequation for and effective application in Leontopithecus chrysomelas. To start investigating the gamete´s epigenetic role in male reproductive success, this essay established a sperm RNA isolation protocol, highlighting the use of seminal clot, a rich source of genetic material, which is usually thrown away after processing. The samples of each individual were condensed in two pools, one referring the clot and other to the liquid fraction. Adaptations for the somatic cellular lyse allowed obtainment of similar profiles between the two portions of the ejaculate. The qualitative profiles for sperm RNA of Leontopithecus chrysomelas indicates low concentration of molecules bigger than RNA, being represented, basically, by little and degraded transcripts due to silencing of gene expression in spermatozoa. The spermatic transcripts have been assigned as the determinant function in reproduction, enrolled with the regulation of female gamete activation and gene expression at the beginning of the embryo development. Furthermore, is has been proposed that the quantity of RNA present in gametes be used as a non-invasive tool for deducing male fertility, since these transcripts reflect on events that occur during cellular differentiation.